COMBINED CONVECTION HEAT TRANSFER THROUGH RECTANGULAR DUCT - Narendra Narve; Ganesh Agalave; Dhnananjay Misal; Bhaskar Gaikwad (International Journal of Innovations in Engineering Research and Technology, 2022)
A convective mode of heat transfer plays an important role in many engineering applications. Combined convection heat transfer involves with free convection heat transfer effects on forced convection. Sidewalls and bottom surface of the duct were subjected to uniform heat flux while top surface was adiabatic.Test section was incorporated with 27 copper constantan thermocouple to measure wall temperatures & 12 to determine heat loss. The range of parameters used were – Gr=105 to 107 , Re = 1000-2300 and Pr=0.7.Air was used as working fluid .From experimental outcome shows that value of Grashof number and Reynolds numbers for air were are considerably greater than the pure forced convection values in the downstream side of flow. It was observed experimentally wall temperature distribution is varying in sidewalls and bottom side. Temperatures are higher on bottomsie than sidewall.